If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -7 = 5x * 9 Reorder the terms: -7 + 3x = 5x * 9 Reorder the terms for easier multiplication: -7 + 3x = 5 * 9x Multiply 5 * 9 -7 + 3x = 45x Solving -7 + 3x = 45x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-45x' to each side of the equation. -7 + 3x + -45x = 45x + -45x Combine like terms: 3x + -45x = -42x -7 + -42x = 45x + -45x Combine like terms: 45x + -45x = 0 -7 + -42x = 0 Add '7' to each side of the equation. -7 + 7 + -42x = 0 + 7 Combine like terms: -7 + 7 = 0 0 + -42x = 0 + 7 -42x = 0 + 7 Combine like terms: 0 + 7 = 7 -42x = 7 Divide each side by '-42'. x = -0.1666666667 Simplifying x = -0.1666666667
| g/3-7=6 | | 4x-3x-2=21 | | -9m+(-6)=93 | | 2=yx+x | | f(x)=100(0.7) | | r/2+8=9 | | 2=yx+y | | 16-3x+5x=180 | | 7m+2m+8m-6= | | .95=logx | | 55*1=n | | 5x-16+3x=180 | | 4x-12=6x-36+14 | | -3x+12= | | -9f+(-32)=-95 | | 3+2h=5 | | 2n+7-7n=33-11n+10 | | 3+-1u=0 | | 2t-4t=8 | | 8g-15=73 | | 1+-4u=0 | | 8c-(-19)=59 | | s=6*7+64t-16t^2 | | 1.5(9x-3)=-4+8x | | h+30=180 | | 8c-(-19)=58 | | 5x+3=-x-2 | | -8+2g=-2 | | 5x+5=-10forx | | 2(w+5)=12 | | 4(x-a)+5b=5x+aforx | | ps+qr=r |